Problems of Establishing Limits for Arsenic Content in Brown Algae and Brown Algae-Containing Medicinal Products - V. M. Shchukin; A. A. Erina; E. A. Lisman; O. A. Vaganova (Регуляторные исследования и экспертиза лекарственных средств)
Algae tend to accumulate elemental toxic substances in high concentrations. Algae are widely used in the food and pharmaceutical industries, and this dictates the need to establish limits for the content of toxic substances that they may contain. The aim of the study was to analyse the requirements of the Russian and foreign pharmacopoeias and other regulatory documents concerning the limits for the content of arsenic in brown algae. The paper presents the results of analysis of monographs from the State Pharmacopoeia of the Russian Federation, XIII and XIV editions, draft version of the Pharmacopoeia of the Eurasian Economic Union, United States Pharmacopoeia, Japanese Pharmacopoeia, European Pharmacopoeia, and Ayurvedic Pharmacopoeia of India containing limits for the content of arsenic in herbal medicinal products (HMPs). In addition, the authors analysed Russian, international and foreign food industry and dietary supplements regulations, as well as scientific publications on arsenic content in brown algae. They also considered the nomenclature of arsenic compounds to be determined and controlled in medicinal products, highlighted the main approaches to and identified global trends in establishing the limits for their content in HMPs. The paper summarises specific aspects of inorganic arsenic compounds accumulation by brown algae. It was demonstrated that the majority of foreign pharmacopoeias either have specific norms for arsenic content in brown algae, which differ from the norms for HMPs, or have general norms that take into account different toxicity levels of organic and inorganic arsenic compounds. There is a tendency to control the content of elemental toxic substances based on their maximum allowable daily intake. The paper substantiates the need for separate determination of toxic inorganic arsenic compounds and potentially toxic methyl arsonate and dimethyl arsinate in HMPs.